2023
DOI: 10.1186/s40352-023-00209-w
|View full text |Cite
|
Sign up to set email alerts
|

Medications for opioid use disorder during incarceration and post-release outcomes

Abstract: Background Continuation or initiation of MOUDs during incarceration could improve post-release outcomes by preventing return to opioid use and reducing risk of overdose. People with OUD involved in the criminal legal system are a vulnerable population, yet little research has comprehensively examined post-release outcomes associated with receiving MOUDs in jail and prison settings. Methods The authors conducted a review of published peer-reviewed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…For those transitioning to the community from justice settings MOUD programs have been shown to reduce mortality due to overdoses. Overall buprenorphine and methadone maintenance have shown decreased rates of overdose, in studies of XR-NTX overdose risk was due to discontinuation of the medication ( Cates and Brown, 2023 ). A current NIDA funded randomized controlled trial comparing XR-NTX to extended-release buprenorphine among persons in jail and prison in 5 states evaluating the primary outcome of retention on treatment post-release and secondary outcomes include recurrence of opioid use and overdose ( Waddell et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For those transitioning to the community from justice settings MOUD programs have been shown to reduce mortality due to overdoses. Overall buprenorphine and methadone maintenance have shown decreased rates of overdose, in studies of XR-NTX overdose risk was due to discontinuation of the medication ( Cates and Brown, 2023 ). A current NIDA funded randomized controlled trial comparing XR-NTX to extended-release buprenorphine among persons in jail and prison in 5 states evaluating the primary outcome of retention on treatment post-release and secondary outcomes include recurrence of opioid use and overdose ( Waddell et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence that MOUD reduces justice involvement ( Belenko et al., 2013 ; Cates and Brown, 2023 ; Keen et al., 2000 ; Oliver et al., 2010 ), it is unknown if it decreases reincarceration ( Evans et al., 2022 ; Haas et al., 2021 ). Some studies focused on OUD treatment have found a decrease in the risk of recidivism for those offered buprenorphine after release ( Evans et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations